Analysis of Ship Radio Frequency Coverage Failure - Sugandi, Budi; Syahidah, Fathiyyah; Ridwan, Ridwan (Politeknik Negeri Batam, 2024)
MF/HF Radio communication equipment is a communication device that uses a medium or high frequency system that is intended for maritime purposes. The device is equipped with a maritime mobile service identity, which has the ability to transmit, receive and monitor distress signals. The device also can be used for normal communication between ship-to-ship and ship-to-land. In this article, we conducted direct monthly testing of MF/HF Radio when sending distress signals. We monitored the problems caused by delays in the process of sending and receiving distress signals when the ship was sailing. The delays occurred due to the Single Side Band MF antenna. To analyze the problem, we propose a qualitative descriptive approach, which describs and analyzes the problems found. We use four categories to analyze the problem which are number of incidents, primary causes of failure, time of incidents and average duration of failure.The experimental results show the results of each category. The frequency coverage failure incidents has eight times incidents. The biggest cause failure was caused by weather interference with 35 % failure. The time of incident was at night time. It was 30 % incidents. And the average duration failure was in two hours with 40%. Using these data, we can prevent and improve the MF/HF radio communication when sending and receiving distress signal optimally. Therefore, in shipping activities especially when carrying out communication activities and facing emergencies, distress signals can be sent and received quickly and accurately.